النص التراثي في ضوء القراءة المعاصرة –قراءة في نصوص أبي حيان التوحيدي - بوعنان, لبنى (جامعة الوادي - university of Eloued, 2020)
يظل كل نص باعتباره كتابة بحاجة إلى قراءة ما، وباعتباره ظاهرة تداولية وثيقة الصلة بسياق إنتاجها ومرجعياتها التاريخية والثقافية والسوسيولوجية، يكون مدعاة لتحريك أفق المتلقي وتشريع أفق التأويل، لذا فإن تلقي النصوص وانفتاحها على القراءة تجعل منها نصوصا خالدة تتجدد وتثمر مع كل قراءة، بخاصة بعد خضوع التراث النقدي العربي لمناهج وآليات جديدة فرضها المنجز النقدي الغربي الحديث، عملت على تفكيك الرموز اللغوية للنص التراثي وشحنه بمفاهيم حداثية انتقلت بالنص من معناه الإبداعي إلى التصور المعاصر للقراءة، ولعل النص التوحيدي يمثل أحد النصوص الأكثر ثراء وتنوعا لما يتميز به هذا النص من لغة موسوعية شمولية تستدعي قراءات متعددة أيضا الأمر الذي يضعنا أمام إشكالية مفادها : هل يختلف فهم ومقاصد النص باختلاف السياق؟ كيف نُخضع النص التراثي لقراءاتنا الراهنة؟ كيف يتفاعل القارئ المعاصر في سياقه الثقافي الراهن مع نص ولّدته سياقات ثقافية مختلفة؟ وما نتيجة هذا الجدل في تأويل المحمول الدلالي له ؟ Abstract: Each text as a writing needs to be read,and as a pragmatic phenomenon closely related in its production to its historical, cultural and social references,is a reason for moving the horizon of interpretation. so,Receiving texts and its opening to reading made them immortal texts, renewing and fruiting with each reading,especially when the Arab critical heritage used new methods and mechanisms imposed by the modern Western critical achievement,worked to dismantle the linguistic symbols of the heritage text and charged with modernist concepts moved the text from the creative meaning to the contemporary vision of reading. Perhaps the monotheistic text is one of the richest and most varied textsAs its language is encyclopedic and global calls for multiple readings, here we ask the following question: do understanding and the purposes of the text differ according todifferent context? How do we submit the heritage text to our current readings? How does the contemporary reader in his current cultural context interact with a text generated by different cultural contexts? What is the result of this controversy in the interpretation of its semantic charge?
مقال
Keywords: النص التراثي، الفهم المعاصر، أبي حيان التوحيدي، سياق الإنتاج، سياق التلقي; The Heritage Text, Contemporary Understanding, Abihyan al-tawhidi, the context of production